Proposed PV Transformer-Less Inverter Topology Technique for Leakage Current Reduction - M. N. H. khan; M.H. Delwar; Md. A. Kabir; M.S. Zahan; K. J. Ahmad; M. M. Alam; M. T. Anower (Institute of Advanced Engineering and Science, 2016)
Importance and demand of using renewable energy is dramatically escalated globally. Hence, the use of renewable energy is going to touch in peak. This demand is varying according to the site choosing. For instance, Wind is preferable where air is following highly as well as solar recommended place is high sun ray reducing places. Especially, the renewable system is highly recommended for electrification issues where it’s possible to produce the electricity for fulfilling rural and remote areas electricity problem. The photovoltaic (PV) panel of connecting with transformer based system is popular where some limitations are occurred especially cost and weight. In contrast, in this paper is focusing these issues where the transformer-less inverter system is used. Here will discuss some transformer-based and transformer-less inverter topologies and the leakage current issue which is occurred when transformer-less inverter system is used. Moreover, here is proposed a topology for reducing the leakage current after doing switching technique in both 50% and 75% duty cycle where output voltage remains quite same.